Design and development of a communication platform with the capability of monitoring the communication quality in a drone separation system for support of U-Space Separation Management Service - Matos, Rui Miguel Lopes Gaspar de (2022)
Dissertação de Mestrado em Engenharia Informática apresentada à Faculdade de Ciências e Tecnologia